Multimodal adaptive cross-mamba for tomato leaf disease diagnosis built on real-world agricultural data - Huinian Li; Nannan Li; Wenmin Wang; Chengcheng Yang; Ningxia Chen; Fuqin Deng; Mengbao Fan (Computers and Electronics in Agriculture, 2026)

Stage-regulation of low light intensity during basal internode formation on maize stalk lodging resistance traits - Fan Liu; Chengcheng Lyu; Pijiang Yin; Chaode Liang; Ye Tao; Cailing Xu; Dongju Feng; Xinglong Wang; Fanlei Kong; Jichao Yuan (Field Crops Research, 2026)

Chirality-engineered nanozymes orchestrate gut microbiota-host metabolism to shield against cardiotoxicity during cancer chemotherapy via the gut-heart axis - Xiaowan Fan; Shuyu Wang; Yuchen Wang; Shuai Han; Xiaoxi Chen; Yingting Huang; Shanzi Qin; Chengcheng Luo; Ying Wang; Xiyun Yan; Kelong Fan; Shipeng Ning (Science Bulletin, 2026)

A dual-network hydrogel loaded with AgNPs/CuMOF exhibits photocatalytic antibacterial activity to promote infected wound healing - Danni Ma; Qian Li; Feng Yang; Chen Zhang; Chengcheng Deng; Ning Fan; Zhangfeng Sun; Xiao Yang; Dongfeng Yin (Chemical Engineering Journal, 2026)

A daily-weekly-resolved δ18O record derived from a modern giant clam shell in the northern South China Sea: Implications for paleoclimate and paleoweather reconstruction - Chengcheng Liu; Nanyu Zhao; Guozhen Wang; Fan Luo; Shan Liu; Qiuju Yang; Murong Qi; Tao Han; Gang Xue; Miaohong He; Qiuli Li; Guoqiang Tang; et al. (Chemical Geology, 2026)

Systematic evaluation reveals the dynamics and functions of horizontal gene transfer widespread in algae - Limin Jia; Liangwei Li; Qijin Ge; Yanchun You; Kai Han; Sibo Wang; Jianwei Chen; Dazhi Wang; Xin Liu; Yunyun Zhuang; Guangyi Fan; Chengcheng Shi (Marine Life Science & Technology, 2026)

Integrated hydrochemical and geochemical modeling of cadmium migration and source apportionment in shallow groundwater - Yuxing Fan; Shuqiong Kong; Zhihao Yi; Weiji Wu; Xiaguo Wei; Junxia Zhang; Yi Wang; Haotian Song; Chengcheng Jia; Hongchen Jiang (Chemical Geology, 2026)

Corrigendum to “Lipid-protein synergistic micronized salt composite: High-pressure homogenization for enhanced sodium dispersion and thermal stability” [Food Chem. 487 (2025) 144825] - Xin Fan; Chengcheng Xu; Yao Qin; Dayong Zhou; Deyang Li (Food Chemistry, 2026)

Danhong Injection targets CaMKII through Dihydrotanshinone I to alleviate cardiomyocyte death and inflammation in viral myocarditis - Junxia Zhang; Chengcheng Zhao; Wenjia Zhang; Mao Zhang; Fan Li; Haibao Shang; Wen Zheng; Yingjia Li; Li Quan; Xiaochuan Li; Huihui Li; Luyun Wang; et al. (Science China Life Sciences, 2026)

Assessing source water reservoirs as pre-treatment units for simultaneous control of autochthonous and runoff pollution through artificial mixing and aeration technology - Nan Li; Wenzhao Hu; Yang Gao; Fan Si; Chengcheng Wen; Lei Lv; Qiyan Wang; Ben Ma; Kai Li; Gang Wen; Tinglin Huang; Haihan Zhang (Water Research, 2026)

Design of alkali-activated MSWI fly ash-based cementitious materials under carbonation curing: Mechanical properties, heavy metal solidification, and mechanisms - An Sai; Wang Baomin; Chen Wenxiu; Fan Chengcheng (Sustainable Chemistry and Pharmacy, 2026)

Synoptic-scale precipitation events recorded by high-resolution intra-shell δ18O of land snail in the Asian monsoon marginal zone - Qian Zhang; Jibao Dong; Guozhen Wang; Fan Luo; Ya-na Jia; Chengcheng Liu; Xiulan Zong; Xiangzhong Li; John Dodson; Hong Yan (Quaternary Science Reviews, 2025)

Unveiling the functional contribution of Malpighian tubule specific glucose transporters to xenobiotics tolerance in Spodoptera litura - Long Jin; Zixin Zhang; Haoran Kong; Chengcheng Fan; Furong Mao; Yiou Pan; Qingli Shang (Pesticide Biochemistry and Physiology, 2025)

Fat body specific ABCG3 accounts for xenobiotic tolerance and is regulated by the homeobox transcription factor Bcd in Spodoptera litura - Lin Liang; Long Jin; Furong Mao; Chengcheng Fan; Haoran Kong; Zixin Zhang; Yiou Pan; Qingli Shang (Pesticide Biochemistry and Physiology, 2025)

Metal-organic frameworks for CO2 capture: Tailoring structure and function through modification strategies - Ke Fan; Yun Wang; Chengcheng Tian; Xiaohong Guan; Xubiao Luo; Yanbo Zhou (Chemical Engineering Journal, 2025)

Comparative study of alcohol co-oxidation for enhanced phenol degradation in wastewater under supercritical water oxidation (SCWO) conditions - Chengcheng Luo; Xiaojuan Fan; Songzhen Tang; Huan Xi (Journal of Water Process Engineering, 2025)

Lipid-protein synergistic micronized salt composite: High-pressure homogenization for enhanced sodium dispersion and thermal stability - Xin Fan; Chengcheng Xu; Yao Qin; Dayong Zhou; Deyang Li (Food Chemistry, 2025)

Preparation of novel cationic porous polymers for effective pre-concentration and sensitive detection of endocrine disruptors in water and fish - Chengcheng Fan; Yanli Dong; Zhi Li; Qianqian Wang; Zhi Wang; Qiuhua Wu; Chun Wang (Analytica Chimica Acta, 2025)

Paleoprecipitation variations from LGM to early-middle Holocene on the southeastern Chinese Loess Plateau: evidence from land snail shells δ13C - Ya-na Jia; Hong Yan; Jibao Dong; Xiulan Zong; Guozhen Wang; Chengcheng Liu; Qian Zhang; Fan Luo; John Dodson (Quaternary Science Reviews, 2025)

New factors driving in-plane uneven degradation of Pt in proton exchange membrane fuel cells at high current density - Kai Han; Xiaolong Li; Rongrong Zhang; Yongzhen Wang; Chao Li; Min Fan; Chengcheng Huang; Hongmei Liu; Zipeng Zhao; Zhaojing Ni (Chemical Engineering Journal, 2025)

Organic modification of synthetic montmorillonite by long- and short-chain quaternary ammonium salt to enhance the thickening ability - Lei Hao; Kaitong Fan; Chengcheng Zhang; Lei Wang; Hong Xu; Jinxiang Dong (Applied Clay Science, 2025)

Immobilization and coordination chemistry of Friedel’s salt (Ca/Al-LDHs) on heavy metals removal - Chengcheng Fan; Baomin Wang; Hu Feng; Hongyu Zhou; Yihan Zhang; Weigao Ding; Fei Liu (Process Safety and Environmental Protection, 2025)

Exploring changes in epibenthic food web structure after implementation of a water-sediment regulation scheme - Yunlong Chen; Chengcheng Su; Xiaomin Zhang; Shuai Cai; Harry Gorfine; Yongqiang Shi; Xiujuan Shan; Fan Li; Xianshi Jin (Science of The Total Environment, 2024)

Integrated scRNAseq analyses of mouse cochlear supporting cells reveal the involvement of Ezh2 in hair cell regeneration - Yifan Zhao; Ze Xu; Ran Zhang; Mingli Liu; Chengcheng Lu; Chunxin Fan; Jian Wang (Molecular Biology Reports, 2024)

Navigability of Liquefied Natural Gas Carriers Along the Northern Sea Route - Long Ma; Sihan Qian; Haihui Dong; Jiemin Fan; Jin Xu; Liang Cao; Shuai Xu; Xiaowen Li; Chengcheng Cai; Yuanyuan Huang; Min Cheng (Journal of Marine Science and Engineering, 2024)
As Arctic sea ice continues to melt and global demand for clean energy rises, Russia’s Liquefied Natural Gas (LNG) exports via the Northern Sea Route (NSR) are rapidly increasing. To ensure the operational safety of LNG carriers and safeguard the economic interests of stakeholders, including shipowners, a thorough assessment of the navigability of various ice-class LNG carriers along this route is essential. This study collected Arctic ice condition data from 2014 to 2023 and applied the Polar Operational Limit Assessment Risk Indexing System (POLARIS) methodology to calculate the Risk Index Outcome (RIO) for LNG carriers with No Ice Class, Arc4, and Arc7 ice classifications in Arctic waters. A navigability threshold of 95% RIO ≥ 0 was established to define navigable windows, and critical waters were identified where sections of the route remain in hazardous or risky conditions year-round. The results indicate that for No Ice Class vessels, Arc4 vessels, and Arc7 vessels, the navigable windows for westbound Route 1 and Route 2 under light, normal, and heavy ice conditions range from 70 to 133 days, 70 to 365 days, and 70 to 365 days, respectively, while for eastbound Route 3, the navigable windows range from 0 to 84 days, 0 to 238 days, and 7 to 365 days, respectively. The critical waters affecting the navigability of No Ice Class vessels, Arc4 vessels, and Arc7 vessels are primarily located in the Kara Sea, Laptev Sea and East Siberian Sea. This study, using the POLARIS methodology, provides valuable insights into the navigability of LNG carriers with different ice classes along the NSR, supporting the development and utilization of Arctic energy and shipping routes while offering decision-making support for stakeholders involved in Arctic maritime operations.

Potential environment effect on ultrahigh resolution Sr/Ca of giant clam shells from South China Sea - Chengcheng Liu; Hong Yan; Liqiang Zhao; Nanyu Zhao; Fan Luo; Hanfeng Wen; Haotian Yang; Wei Yang; Jialong Hao; Chengde Liang; Kentaro Tanaka; Naoko Murakami-Sugihara; et al. (Coral Reefs, 2024)

Geochemical characteristics of uranium-rich dispersed organic matter and their geological significance for uranium mineralization: A case study from the Ordos Basin - Fan Zhang; Yangquan Jiao; Liqun Wu; Hui Rong; Jianying Wang; Chengcheng Zhang (Journal of Geochemical Exploration, 2024)

Preparation of ionic porous polymers for extraction of four phenolic endocrine disrupting chemicals from fish and water samples - Chengcheng Fan; Chenhuan Wang; Bin Zhao; Zixuan Cai; Qianqian Wang; Lin Hao; Zhi Wang; Qiuhua Wu; Chun Wang (Food Chemistry, 2024)

Soliton solution, breather solution and rational wave solution for the coupled macroscopic fluctuation theory equation in the optimal path of the process - Li Li; Chengcheng Fan; Fajun Yu (Wave Motion, 2024)

Quantitative reconstruction of a single super rainstorm using daily resolved δ18O of land snail shells - Guozhen Wang; Jibao Dong; Tao Han; Chengcheng Liu; Fan Luo; Haotian Yang; Miaohong He; Guoqiang Tang; Nanyu Zhao; Qian Zhang; Gang Xue; John Dodson; et al. (Science Bulletin, 2024)

Plant regeneration through two pathways of direct organogenesis in Paeonia ostii ‘Feng Dan’ - Chengcheng Fan; Kexin Li; Li Xu; Zhijun Deng; Shiming Deng; Jitao Li; Jiaolin Mou (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Preparation of geopolymer based on municipal solid waste incineration fly ash-phosphorus slag and its function for solidification of heavy metals - An Sai; Wang Baomin; Chen Wenxiu; Yu Ze; Fan Chengcheng (Waste Management, 2024)

Solidification/stabilization and optimization of municipal solid waste incineration fly ash with aluminosilicate solid wastes - Chengcheng Fan; Weigao Ding; Baomin Wang (Journal of Environmental Management, 2024)

Improved yield by optimizing carbon, nitrogen metabolism and hormone balance in apical kernels under low nitrogen conditions using the low nitrogen–tolerant maize variety - Qinlin Liu; Xinglong Wang; Yawei Wu; Tianqiong Lan; Fan Liu; Gui Wei; Chengcheng Lv; Fanlei Kong; Jichao Yuan (Field Crops Research, 2024)

Molybdenum and cadmium cause blood–testis barrier dysfunction through ROS-mediated NLRP3 inflammasome activation in sheep - Lu Jiang; Fan Yang; Huan Liao; Weiwei Chen; Xueyan Dai; Chengcheng Peng; Zhiyuan Li; Huating Wang; Tao Zhang; Huabin Cao (Science of The Total Environment, 2024)

Solidification of municipal solid waste incineration fly ash with alkali-activated technology - Chengcheng Fan; Zhenlin Wu; Baomin Wang; Weihao Zheng (Journal of Environmental Management, 2023)

A novel method for solidification/stabilization of MSWI fly ash by graphene nanoplatelets synergistic alkali-activated technology - Tianru Li; Baomin Wang; Xiong Zhang; Xiao Han; Yunqing Xing; Chengcheng Fan; Ze Liu (Journal of Environmental Chemical Engineering, 2023)

Role of Caveolin-1 on the molybdenum and cadmium exposure induces pulmonary ferroptosis and fibrosis in the sheep - Tao Zhang; Fan Yang; Xueyan Dai; Huan Liao; Huating Wang; Chengcheng Peng; Zirui Liu; Zhiyuan Li; Jiyi Shan; Huabin Cao (Environmental Pollution, 2023)

Comparative Pollution Toxicity and Chemical Speciation of Heavy Metals in MSWI Fly Ash with Different Particle Size Distribution - Chengcheng Fan; Baomin Wang; Yi Xu; Hainan Ma; Ze Liu (Water, Air, & Soil Pollution, 2023)

Effect of nano silica on solidification/stabilization of heavy metal in alkali-activated MSWI fly ash solidified body - Tianru Li; Baomin Wang; Xiong Zhang; Xiao Han; Yunqing Xing; Chengcheng Fan; Ze Liu (Process Safety and Environmental Protection, 2023)

Daily growth rate variation in Tridacna shells as a record of tropical cyclones in the South China Sea: Palaeoecological implications - Nanyu Zhao; Hong Yan; Fan Luo; Yuanjian Yang; Shan Liu; Pengchao Zhou; Chengcheng Liu; John Dodson (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Crosstalk between Mfn2-mediated mitochondria associated membranes disorder and autophagy induced by molybdenum and cadmium in sheep heart - Chengcheng Peng; Shuqiu Yang; Fan Yang; Zhiwei Xiong; Qiang Liu; Shuxian Liao; Kai Huang; Wengen Wan; Huabin Cao (Food and Chemical Toxicology, 2023)

Dynamics of global dryland vegetation were more sensitive to soil moisture: Evidence from multiple vegetation indices - Huanhuan Liu; Yue Liu; Yu Chen; Mengen Fan; Yin Chen; Chengcheng Gang; Yongfa You; Zhuonan Wang (Agricultural and Forest Meteorology, 2023)

Symbiont-screener: A reference-free tool to separate host sequences from symbionts for error-prone long reads - Mengyang Xu; Lidong Guo; Yanwei Qi; Chengcheng Shi; Xiaochuan Liu; Jianwei Chen; Jinglin Han; Li Deng; Xin Liu; Guangyi Fan (Frontiers in Marine Science, 2023)
Metagenomic sequencing facilitates large-scale constitutional analysis and functional characterization of complex microbial communities without cultivation. Recent advances in long-read sequencing techniques utilize long-range information to simplify repeat-aware metagenomic assembly puzzles and complex genome binning tasks. However, it remains methodologically challenging to remove host-derived DNA sequences from the microbial community at the read resolution due to high sequencing error rates and the absence of reference genomes. We here present Symbiont-Screener ( https://github.com/BGI-Qingdao/Symbiont-Screener ), a reference-free approach to identifying high-confidence host’s long reads from symbionts and contaminants and overcoming the low sequencing accuracy according to a trio-based screening model. The remaining host’s sequences are then automatically grouped by unsupervised clustering. When applied to both simulated and real long-read datasets, it maintains higher precision and recall rates of identifying the host’s raw reads compared to other tools and hence promises the high-quality reconstruction of the host genome and associated metagenomes. Furthermore, we leveraged both PacBio HiFi and nanopore long reads to separate the host’s sequences on a real host-microbe system, an algal-bacterial sample, and retrieved an obvious improvement of host assembly in terms of assembly contiguity, completeness, and purity. More importantly, the residual symbiotic microbiomes illustrate improved genomic profiling and assemblies after the screening, which elucidates a solid basis of data for downstream bioinformatic analyses, thus providing a novel perspective on symbiotic research.

The study of road deformation induced by ground fissure in Xi’an, Central China - Wen Fan; Xianglin Peng; Longsheng Deng; Chengcheng Jiang (Arabian Journal of Geosciences, 2020)

Fluorine-modified sialyl-Tn-CRM197 vaccine elicits a robust immune response - Chengcheng Song; Xiu-Jing Zheng; Haili Guo; Yafei Cao; Fan Zhang; Qin Li; Xin-Shan Ye; Yifa Zhou (Glycoconjugate Journal, 2019)

Effect of selenium supplements on the antioxidant activity and nitrite degradation of lactic acid bacteria - Yang Chen; Qin Li; Chengcheng Xia; Fan Yang; Ning Xu; Qian Wu; Yong Hu; Lusha Xia; Chao Wang; Mengzhou Zhou (World Journal of Microbiology and Biotechnology, 2019)

Fast ambiguity resolution for long-range reference station networks with ionospheric model constraint method - Ming Zhang; Hui Liu; Zhengdong Bai; Chuang Qian; Chengcheng Fan; Peng Zhou; Bao Shu (GPS Solutions, 2017)

Impacts of Nomad Sedentarization on Social and Ecological Systems at Multiple Scales in Xinjiang Uyghur Autonomous Region, China - Mingming Fan; Wenjun Li; Chengcheng Zhang; Lanhai Li (Ambio, 2014)

Synthesis, Crystal Structure and Photoluminescence of a Cyclometalated Iridium(III) Coumarin Complex - Tianzhi Yu; Chengcheng Zhang; Yuling Zhao; ShaoQiang Guo; Peng Liu; Wentao Li; Duowang Fan (Journal of Fluorescence, 2013)

DNMT3A rs36012910 A>G polymorphism and gastric cancer susceptibility in a Chinese population - Qunying Wu; Sen Lu; Ling Wang; Jiaojiao Hu; Fengchang Qiao; Xuemei Qiu; Chengcheng Zhao; Yingbin Lao; Yunwei Song; Hong Fan (Molecular Biology Reports, 2012)

A PCA-based method for construction of composite sustainability indicators - Tao Li; Hongchao Zhang; Chris Yuan; Zhichao Liu; Chengcheng Fan (The International Journal of Life Cycle Assessment, 2012)